Former Yugoslav Republic of Macedonia : First Review Under the Stand-By Arrangement and Request for Waiver of Applicability of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2003)
Macedonia's macroeconomic stabilization program continues to rest on the basis of fiscal and monetary policies, and has restored the fiscal balance to a sustainable level after two years of high deficits. Further structural measures are important to address impediments to growth and to reduce unemployment. Reforms are necessary to strengthen the investment climate by creating a predictable business environment, implementing judicial reforms, and addressing governance problems. The financial system stability assessment acknowledged the authorities' efforts to improve the soundness of the banking system and to address remaining vulnerabilities.